2015
DOI: 10.1111/dar.12290
|View full text |Cite
|
Sign up to set email alerts
|

Associations between emotional distress and heavy drinking among young people: A longitudinal study

Abstract: IntroductionDepression has generally been found to be associated with heavy drinking and alcohol use disorders [1][2][3][4]. There is also evidence of a link between anxiety and extensive use of alcohol [5][6][7][8], but this association has been less extensively scrutinized and the findings seem less clear. Thus, some studies of young people report null-findings [9] or a link between anxiety and heavy drinking that is attributable to concurrent symptoms of depression and/or other confounding factors [10][11][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(79 reference statements)
0
7
1
Order By: Relevance
“…Despite the exclusion of women with depressive symptoms at baseline, the reverse association is still possible (that poor mental health leads to binge drinking) and has been supported by several studies (Bell and Britton, 2014;Pape and Norström, 2015). Others have supported a bidirectional relationship between alcohol dependence and depression (Brière et al, 2014;Bulloch et al, 2012), or that heavy and/or binge drinking precedes depression (Fergusson et al, 2009;Paljarvi et al, 2009;Wang and Patten, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the exclusion of women with depressive symptoms at baseline, the reverse association is still possible (that poor mental health leads to binge drinking) and has been supported by several studies (Bell and Britton, 2014;Pape and Norström, 2015). Others have supported a bidirectional relationship between alcohol dependence and depression (Brière et al, 2014;Bulloch et al, 2012), or that heavy and/or binge drinking precedes depression (Fergusson et al, 2009;Paljarvi et al, 2009;Wang and Patten, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although causality in observational data is not easy to infer, a range of techniques such as cross-contextual comparisons, negative controls, sensitivity analysis for unmeasured confounders, instrumental variable analysis or Mendelian Randomization [101,102], and fixed-effect models that eliminate time-invariant confounders [103] can be used for more robust causal inference. To the best of our knowledge, only two articles in this area have applied fixed-effect models [104,105]. However, their exposure and outcome were measured within the same period and the direction of the association they found could be from alcohol use behaviours to mental health problems [104,106].…”
Section: Other Implications For Future Studiesmentioning
confidence: 99%
“…While some longitudinal studies have linked early depressive symptoms to later alcohol use [14], other studies have not found this association [15,16]. In terms of alcohol problems, evidence suggests that these are generally preceded by depressive symptoms [17–21].…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the complexity of the association between alcohol use and depression remains limited [17,21,22], but there is reason to believe that early onset of alcohol use, and high levels of alcohol use is associated with later poor mental health, as well as functional, economic and social problems [23–31]. However, variability in alcohol use trajectories may be differentially associated with symptoms of depression.…”
Section: Introductionmentioning
confidence: 99%